Final Height and Associated Factors in Perinatally HIV-infected Asian Adolescents. Issue 2 (February 2016) - Bunupuradah, Torsak; Kariminia, Azar; Aurpibul, Linda; Chokephaibulkit, Kulkanya; Hansudewechakul, Rawiwan; Lumbiganon, Pagakrong; Vonthanak, Saphonn; Vibol, Ung; Saghayam, Suneeta; Nallusamy, Revathy; Van Nguyen, Lam; Yusoff, Nik Khairulddin N.; et al.
Abstract : We analyzed final height of 273 perinatally HIV-infected Asian adolescents older than 18 years at their last clinic visit. By the World Health Organization child growth reference, 30% were stunted, but by the Thai child growth reference, 19% were stunted. Half of those who were stunted at antiretroviral therapy initiation remained stunted over time. Being male and having a low baseline height-for-age Z score of less than −1.0 were associated with low final height Z score.